The Influence of Work Culture, Compensation and Work Spirit on Employee Performance of Health Office in in Pariaman City - Dahlila Dahlila; Aldri Frinaldi (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The biggest challenge for local governments in realizing the success of health development as well as the biggest hope is how to manage human resources (HR) dynamic, productive hard worker to achieve Indonesia's Vision 2045. The Health Office as OPD that handles the health sector has not yet reached the work target according to the predetermined work plan. To achieve the highest degree of health requires hard work in the health sector. This study is to reveal the influence of work culture, compensation and employee morale in the Pariaman City Health Office. With quantitative methods and a saturated sample of 62 employees, questionnaires, interviews and observations were carried out. Data testing was carried out with validity and reliability. The results of the path analysis state that there are direct and indirect effects of exogenous variables on endogenous variables.There is an influence of work culture, compensation and work morale on the performance of the employees of the Kota Pariaman Health Office by 55% and an indirect effect of 31.6%. The rest is influenced by other variables not examined in this study.